1985
DOI: 10.1177/019251218500600408
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Success of New Parties

Abstract: After describing the universe of 233 new parties formed in 19 West European and Anglo-American democracies from 1960 through 1980, the authors use data on those parties to address several hypotheses concerning system-level causes and conditions for new party formation and electoral success. It is found that although the propensi ty for forming new parties is not associated with structural variables, new party suc cess is related to the type of electoral system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
134
1
42

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(178 citation statements)
references
References 14 publications
1
134
1
42
Order By: Relevance
“…It has been commonly assumed or concluded that the demand for new parties is related to social heterogeneity, social or value change in a country, or the rise of new issues inadequately represented by established parties (see Harmel & Robertson 1985, Hauss & Rayside 1978, Müller-Rommel 2002, Kitschelt 1988, Hug 1996). Ferdinand Müller-Rommel's review of Hug (2001) underscores the point: 'we know that new parties emerge primarily because old parties have failed to absorb new issues into their agendas and programmes ' (2002: 741).…”
mentioning
confidence: 99%
“…It has been commonly assumed or concluded that the demand for new parties is related to social heterogeneity, social or value change in a country, or the rise of new issues inadequately represented by established parties (see Harmel & Robertson 1985, Hauss & Rayside 1978, Müller-Rommel 2002, Kitschelt 1988, Hug 1996). Ferdinand Müller-Rommel's review of Hug (2001) underscores the point: 'we know that new parties emerge primarily because old parties have failed to absorb new issues into their agendas and programmes ' (2002: 741).…”
mentioning
confidence: 99%
“…As Duverger's Law asserts, multiple, smaller parties are more common where electoral structures do not penalize them; district magnitude, electoral formula, and the size of legislature lower the barriers to entry for small parties and are generally recognized as the most significant factors determining the number of parties in a system (see Harmel and Robertson 1985;Hug 2001;Lijphart 1994;Salmond 2006;Taagepera and Shugart 1989;Tavits 2008). Thus, I hypothesize that women's parties are more likely to emerge where these structural features suggest greater opportunity for larger numbers of parties in general.…”
Section: Theory/hypothesesmentioning
confidence: 99%
“…The structural conditions of the emergence and success of new parties is an established field of political party research (Harmel and Robertson, 1985;Ignazi 1996;Tavits, 2006;Bolleyer and Bytzek, 2013). In the case of movement or new politics parties, the presence of a strong social movement is also regarded as a structural condition, which facilitates the emergence of parties (Kitschelt, 1989;Kaelberer, 1998;Burchell, 2002).…”
Section: Introductionmentioning
confidence: 99%